Mobile, Ubiquitous, and Intelligent Computing MUSIC 2013 - Park, James J. (Jong Hyuk).; Adeli, Hojjat; Park, Namje; Woungang, Isaac; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
MUSIC 2013 will be the most comprehensive text focused on the various aspects of Mobile, Ubiquitous and Intelligent computing. MUSIC 2013 provides an opportunity for academic and industry professionals to discuss the latest issues and progress in the area of intelligent technologies in mobile and ubiquitous computing environment. MUSIC 2013 is the next edition of the 3rd International Conference on Mobile, Ubiquitous, and Intelligent Computing (MUSIC-12, Vancouver, Canada, 2012) which was the next event in a series of highly successful International Workshop on Multimedia, Communication and Convergence technologies MCC-11 (Crete, Greece, June 2011), MCC-10 (Cebu, Philippines, August 2010).
A Novel Ranking Technique based on Page Queries; Gwangbum Pyun, Unil Yun -- Ranking Book Reviews based on User Discussion; Heungmo Ryang, Unil Yun -- The Blog Ranking Algorithm using Analysis of both Blog Influence and Characteristics of Blog posts; Jiwon Kim, Unil Yun -- Frequent Graph Mining based on Multiple Minimum Support Constraints; Gangin Lee, Unil Yun -- Design of Automatic Paper Identification System with QR code for Digital Forensics; Ha-Kyung Jennifer Lee, Young-Mi Yun, Kee-Hyung Yoon, Dong-Sub Cho -- Processing Continuous Range Queries with Non-Spatial Selections; HaRim Jung, Seongkyu Kim, Joon-Min Gil, Ung-Mo Kim -- DSPI : An Efficient Index for Processing Range Queries on Wireless Broadcast Stream; Kwanho IN, Seongkyu Kim, Ung-Mo Kim -- End-to-End High Speed Forward Error Correction using Graphics Processing Units; Shohidul Islam, Jongmyon Kim -- Direct Space: A Collaborative Framework for Supporting Group Workspaces over Wi-Fi Direct; Park Jone-Eun, Park Jong-Moon, Myung-Joon Lee -- Specification of Communication Based Train Control System Using AADL; Lichen zhang, Bingqing Xu -- An Agent Modeling for Overcoming the Heterogeneity in the IoT with Design Patterns; Euihyun Jung, Ilkwon Cho, Sun Moo Kang.
Keywords: Engineering; Computer science; Telecommunication; Engineering; Communications Engineering, Networks; User Interfaces and Human Computer Interaction; Computer Engineering